THU0397 Safety and Survival of Rituximab Treatment in Systemic Lupus Erythematosus Versus Rheumatoid Arthritis Patients: A 10 Years Observational Study. (9th June 2015) - Perricone, C.; Ceccarelli, F.; Morello, F.; Alessandri, C.; Spinelli, F.R.; Massaro, L.; Pacucci, V.A.; Scirocco, C.; Priori, R.; Valesini, G.; Conti, F.
Abstract : Background: The anti-CD20 monoclonal antibody rituximab (RTX) is an effective treatment option for patients with systemic lupus erythematosus (SLE) refractory to conventional therapies. The safety of this drug has been widely analyzed in randomized controlled clinical trials in patients with rheumatoid arthritis (RA); on the contrary, there are few data on patients with SLE. Objectives: We aimed to evaluate the safety and survival of treatment with RTX in patients with SLE and RA in a 10 years observational study. Methods: We evaluated the clinical history and laboratory data of patients with SLE (1997 ACR revised criteria) and RA (2010 revised EULAR/ACR criteria) treated with RTX in the period between 2003 and 2013. In all the patients RTX was administered intravenously (IV) according to two different protocols: 1000 mg IV on days 1 and 14, or 375 mg/m 2 on days 1, 8, 15, and 22. Each protocol provided for additional cycles of treatment after an interval of at least 6 months. All patients in both groups received oral acetaminophen (1000 mg), methylprednisolone (125 mg IV), and chlorphenamine (10 mg IV) 30 minutes before each infusion to prevent infusion-related adverse events. Written informed consent was obtained from all patients enrolled in the study. In particular, we analyzed the following parameters: duration of therapy, number of cycles, interval between them, infusion-related (IR) and other adverse events leading to discontinuation of RTX treatment. Statistical analysis was performed using the Mann-Whitney test and Fisher's exact test; the risk was calculated by dividing the number of events by the number of cases. Results: Thirty-three patients with SLE (2M/31F, mean age 41.9±12.1 years, mean disease duration 183.6±74.4 months) and 80 RA patients (15M/65F; mean age 57.5±12.2 years; disease duration 151.2±81.6 months) were treated with RTX. SLE patients were significantly younger compared with RA patients (P<0.0001). SLE patients underwent a total of 87 cycles of therapy (2.6 cycles/patient), compared to 235 in patients with RA (2.93 cycles/patient). The mean duration of treatment was higher in SLE patients than in those with RA (32.7±19.4 months versus 25.5±16.9 months, P=NS). The assessment of the safety profile showed a risk of infusion reactions (IR) significantly higher in patients with RA compared with SLE [12.5% (10/80) versus 3% (1/33); P=0.0007]. In all cases, these events were mild and did not require hospitalization. These IR occurred in 72.7% of cases (8/11) during the first cycle. Concerning other adverse events, only one patient with SLE (3%) developed an infectious disease that caused treatment discontinuation (Legionella Pneumophila pneumonia). No infectious events resulted in treatment discontinuation in patients with RA. Conclusions: The results of our study highlight the long-term safety of treatment with RTX in patients with SLE and RA, with a low risk of infusion-related as well as infectious adverse events. The lower incidence of infusion-related AEs in the SLE patients might be related to the higher-dosage steroid therapy they received during the week before RTX infusion. Finally, physicians should be aware that IR adverse events are more likely to occur during the first cycle of therapy. Disclosure of Interest: None declared